Effects of screening for anxiety and depression in patients with ischaemic heart disease – a nationwide Danish register study. Issue 2 (March 2023) - Kruse, Marie; Laudicella, Mauro; Olsen, Kim Rose; Zwisler, Ann Dorthe O.; Helmark, Charlotte; Pedersen, Susanne S.
Aim: To investigate the effect of screening for anxiety and depression (AD) in patients with ischaemic heart disease (IHD) on the likelihood of receiving treatment for AD. Methods: We used a nationwide dataset of all Danish patients with an incident IHD diagnosis in the period 2015–2018 ( N = 80, 701) of which 20, 461 (25%) were exposed to screening for AD as part of cardiac rehabilitation. A binary composite indicator for the use of any AD treatment (prescriptions of AD drugs, general practitioner (GP) counselling or referral to a psychologist), was modelled as the dependent variable. The probability of receiving AD treatment was estimated using linear probability and instrumental variable regression models. Results: Exposure to AD screening was lower for patients with low income (change in probability −0.67, 95% CI −0.76; −0.59), low education (change in probability −0.16, 95% CI −0.20; −0.13), and a high comorbidity burden (change in probability −0.09, 95% CI −0.10; −0.07). Screened patients had a lower conditional probability of AD treatment (change in probability −0.0061, p < 0.001) than non-screened patients. The patient's GP also had an impact on the probability of being referred for AD treatment. Using an instrumental variable approach did not affect the results. Conclusions: Screening for AD was subject to selection at the patient level; patients at lower risk of AD had a higher probability of being screened. Hence, extending systematic screening to cover a larger population may not achieve a noticeable increase in the uptake of AD treatment if it is not supported by appropriate measures to reduce reverse selection into screening.